2021
DOI: 10.1186/s12877-021-02283-x
|View full text |Cite
|
Sign up to set email alerts
|

Transitions between levels of dependency among older people receiving social care – a retrospective longitudinal cohort study in a Swedish municipality

Abstract: Background Knowledge is scarce on how needs for home help and special housing evolve among older people who begin to receive support from municipal social care. The purpose of this study was to describe baseline distributions and transitions over time between levels of dependency among older persons after being granted social care in a Swedish municipality. Methods Based on a longitudinal cohort study in a Swedish municipality, data was collected r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…These findings correlate with results of a longitudinal Swedish study that examined transitions between levels of dependency among 415 older people receiving supportive care over time [10]. Here, it was reported that a significant number of participants who were initially more dependent, transferred to a lower level of dependency (28%) within one year demonstrating improvements in overall health and quality of life [10]. However, it was also noted that 34% of participants with mild or moderate dependency transitioned to higher dependency levels within the same year [10].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These findings correlate with results of a longitudinal Swedish study that examined transitions between levels of dependency among 415 older people receiving supportive care over time [10]. Here, it was reported that a significant number of participants who were initially more dependent, transferred to a lower level of dependency (28%) within one year demonstrating improvements in overall health and quality of life [10]. However, it was also noted that 34% of participants with mild or moderate dependency transitioned to higher dependency levels within the same year [10].…”
Section: Discussionsupporting
confidence: 77%
“…Here, it was reported that a significant number of participants who were initially more dependent, transferred to a lower level of dependency (28%) within one year demonstrating improvements in overall health and quality of life [10]. However, it was also noted that 34% of participants with mild or moderate dependency transitioned to higher dependency levels within the same year [10].…”
Section: Discussionmentioning
confidence: 95%
“…As the aging population continues to grow and individuals continue to live longer, the complexity of care needs and health issues also increases, often involving multiple health conditions 19 . To continue to meet these changing needs and adhere to the wish of older adults to age in place, care provision and health care interventions also become more complex.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore using only any single dependency measure to understand the complexity and heterogeneity of the dependency of older adults is not sufficient. Also, during the ageing process, older adults will experience a dependency transition, meaning that as age progresses, the dependency status of older adults will change from mild to severe dependency [ 15 17 ]. Hence, a better understanding of the diversity of functional activities may contribute to the knowledge about the heterogeneity of dependency.…”
Section: Introductionmentioning
confidence: 99%